Are we ready to use oxidative stress in clinical practice?. Issue 2 (10th December 2012) - Grabowski, Marcin
Abstract See accompanying article http://dx.doi.org/10.1002/ejlt.201200107 The relationship between atherosclerosis, intravascular inflammation, and oxidative stress has fascinated scientists and clinicians for a long time and is still the subject of continuing research. The hypothesis is very attractive, both from the pathophysiological and therapeutic point of view and has perspective for new therapeutic strategies.